Resisting Postmodernity: Swedish social policy in the 1990s - Arthur Gould (Social Work and Society, 2005)
The purpose of this paper is to introduce ideas that have emerged during the course of writing a book on Swedish welfare in the 1990s. The book is the result of many years of writing about two subjects: Swedish drug policy and the Swedish welfare state. The one very specialised, the other, more general. I first became interested in Swedish drug policy on a research visit to Örebro Län in 1986. A social worker showed me a copy of the county's drug policy programme and explained the significance of the 'restrictive line'. I have spent the years since that visit, trying to understand and explain the Swedish goal of a drug-free society (Gould 1988, 1994, 1996b). I only began to write about the welfare state in Sweden in the early 1990s, just as things were beginning to go wrong for the economy (Gould 1993a, 1993b, 1996a, 1999). For the last few years I have intended to write a book on the events covered by the period 1991-1998 - the years of a Bourgeois and a Social Democratic Government -which would bring the two halves of my work together. Material for this study has been accumulated over many years. A number of research visits have been made; large numbers of academics, politicians, civil servants, journalists, unemployed people, social workers and their clients have been interviewed; and extensive use has been made of academic, administrative and public libraries. Since September 1991 I have systematically collected articles from Dagens Nyheter about social services, social insurance, health care, employment, social issues and problems, the economy and politics. The journal Riksdag och Departement (Parliament and Ministry), which summarises a wide range of public documents, has been invaluable. Friends and informal contacts have also given me insights into the Swedish way of life. The new book is based upon all of these experiences. This paper will begin with a brief account of major global social and economic changes that have occurred in the last twenty years. This is intended to provide a background to the more recent changes that have occurred in Swedish society in the last decade. It will be suggested that the changes in Sweden, particularly in the field of welfare, have been less severe than elsewhere and that this is due to political, institutional and cultural resistance. The paper will conclude by arguing that Sweden, as an exemplar of an Apollonian modern society, has had much to fear from the Dionysian characteristics of postmodernity.